Kebijakan Penanganan Pengungsi di Indonesia Perspektif MaqÄá¹£id Al-SyarÄ«â€™ah - Yulianto, Rohmad Adi (Fakultas Syariah IAIN Purwokerto, 2019)
The problematic of humanism in many countries resulted in a phenomenon of transnational refugee migration. Indonesia is one of a country which has received a massif influx of refugee waves aimed to obtain asylum. This study discussed the policy of handling refugees in Indonesia from the maqasid sharia as perspective. Maqasid sharia, as one of the Islamic law methodological approaches, helped of understanding social phenomena which positioned the interest (maslaha) as the core treatise. This study aimed to explain that the interaction between maqasid sharia as perspective and the development of national regulation, included the regulation in handling refugees, resulted in three models of policy (instructive, integrative, and adaptive). The instructive policy implemented through taqnin model, which is issued by the state authority as a positive norm. An integrative policy implemented through the eclectic model adopted the finest part from both national law and Islamic law. The adaptive policy implemented when important elements of Islamic law affirmed national policy which contained fundamental principles of universal humanism as part of sharia.